PENERAPAN KOMPRES LIDAH BUAYA (ALOEVERA) TERHADAP PENURUNAN SUHU TUBUH PADA BALITA DEMAM DI KLINIK PRATAMA MAHDARINA KOTA MEDAN TAHUN 2025 - Natalia, Kristin -; Nasution, Naimah (Jurnal Pengabdian Masyarakat Putri Hijau, 2025)
Fever is a natural reaction of the body to an inflammatory infection in the body. Fever is one of the common reasons parents should take their children to the nearest hospital. The cause of fever in toddlers is a change in the heat center (thermoregulation) and an infection of a disease that attacks the body's system. The use of aloe vera compresses is one alternative way to lower the body temperature of toddlers with fever. Aloe vera contains saponin chemicals so that it is more useful in compresses, helping the body release heat faster. The use of aloe vera compresses as an alternative therapy in reducing children's fever is still not widely known by mothers who have toddlers, this is due to the lack of knowledge of mothers about aloe vera compresses. Therefore, it is necessary to provide education or counseling again to increase mothers' insight and reduce the incidence of fever in toddlers.